\(\frac{x+1}{60}=\frac{\left(-15\right)}{x+1}\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a/ -4x(x - 5) - 2x(8 - 2x) = -3
=> -4x2 + 20x - 16x + 4x2 = -3
=> 4x = -3
=> x = -3/4
b/ \(\frac{x-1}{-15}=-\frac{60}{x-1}\Rightarrow\left(x-1\right)^2=\left(-60\right)\left(-15\right)\)
\(\Rightarrow\left(x-1\right)^2=900\Rightarrow\orbr{\begin{cases}x-1=30\\x-1=-30\end{cases}\Rightarrow\orbr{\begin{cases}x=31\\x=-29\end{cases}}}\)
Vậy x = -29 , x = 31
\(\left(1-\frac{1}{3}\right)\)\(x\left(1-\frac{1}{6}\right)\)\(x\)\(\left(1-\frac{1}{10}\right)\)\(x\)\(\left(1-\frac{1}{15}\right)\)\(x\)\(\left(1-\frac{1}{21}\right)\)\(x\)\(\left(1-\frac{1}{28}\right)\)\(=\)\(\left(\frac{3}{3}-\frac{1}{3}\right)\)\(x\)\(\left(\frac{6}{6}-\frac{1}{6}\right)\)\(x\)\(\left(\frac{10}{10}-\frac{1}{10}\right)\)\(x\)\(\left(\frac{15}{15}-\frac{1}{15}\right)\)\(x\)\(\left(\frac{21}{21}-\frac{1}{21}\right)\)\(x\)\(\left(\frac{28}{28}-\frac{1}{28}\right)\)\(=\)\(\frac{2}{3}x\frac{5}{6}x\frac{9}{10}x\frac{14}{15}x\frac{20}{21}x\frac{27}{28}\)\(=\)\(\frac{2x5x9x14x20x27}{3x6x10x15x21x28}\)\(=\)\(\frac{2x5\left(3x3\right)x\left(2x7\right)x\left(5x4\right)x\left(3x3x3\right)}{3x\left(3x2\right)x\left(5x2\right)x\left(5x3\right)x\left(7x3\right)x\left(4x7\right)}\)\(=\)\(\frac{3}{7}\)
Áp dụng \(\frac{1}{n\left(n+1\right)}=\frac{1}{n}-\frac{1}{n+1}\) rút gọn rồi quy đồng làm nốt
\(1\frac{13}{15}\cdot\left(0,5\right)^2\cdot3-\left(\frac{8}{15}+1\frac{19}{60}\right):1\frac{19}{60}\)
\(=\frac{28}{15}\cdot\frac{1}{4}\cdot\frac{3}{1}-\frac{37}{20}\cdot\frac{60}{79}\)
\(=\frac{7}{5}-\frac{111}{79}\)
\(=\frac{-2}{395}\)
=28/15.1/4.3-8/15-79/60.60/79
=7.4/15.1/4.3-8/15-1
=7/15.3-8/15-1
=21/15-8/15-1
=13/15-1
=-2/15
\(\left(x+\frac{1}{3}\right)+\left(x+\frac{1}{15}\right)+....+\left(x+\frac{1}{575}\right)=11x+\left(\frac{1}{3}+\frac{1}{9}+\frac{1}{27}+\frac{1}{81}+\frac{1}{243}\right)\)
\(13x+\left(\frac{1}{1.3}+\frac{1}{3.5}+.....+\frac{1}{23.25}\right)=11x+\left(\frac{1}{3}+\frac{1}{9}+\frac{1}{27}+\frac{1}{81}+\frac{1}{243}\right)\)
\(13x+\frac{1}{2}.\left(\frac{1}{1}-\frac{1}{25}\right)=11x+\left(\frac{1}{3}+\frac{1}{9}+\frac{1}{27}+\frac{1}{81}+\frac{1}{243}\right)\)
\(2x+\frac{12}{25}=\frac{1}{3^1}+\frac{1}{3^2}+\frac{1}{3^3}+\frac{1}{3^4}+\frac{1}{3^5}\)
Đặt \(A=\frac{1}{3^1}+\frac{1}{3^2}+\frac{1}{3^3}+\frac{1}{3^4}+\frac{1}{3^5}\)
\(3A=1+\frac{1}{3^1}+\frac{1}{3^2}+\frac{1}{3^3}+\frac{1}{3^4}\)
\(3A-A=1-\frac{1}{3^5}=\frac{242}{243}=2A\)
=> \(A=\frac{121}{243}\)
=> \(2x+\frac{12}{25}=\frac{121}{243}\)
=> \(2x=\frac{121}{243}-\frac{12}{25}=\frac{109}{6075}\)
=> x = ......
\(\frac{x+1}{60}=\frac{\left(-15\right)}{x+1}\)
\(\Rightarrow\left(x+1\right).\left(x+1\right)=\left(-15\right).60\)
\(\Rightarrow\left(x+1\right).\left(x+1\right)=-900\)
\(\Rightarrow\left(x+1\right)^2=-900\)
\(\Rightarrow\left(x+1\right)^2=\left(-300\right).300\)
\(\Rightarrow\left(x+1\right)^2=300^2\)
\(\Rightarrow\orbr{\begin{cases}x+1=300\\x+1=-300\end{cases}\Rightarrow\orbr{\begin{cases}x=299\\x=-301\end{cases}}}\)
Ta co :
\(\frac{x+1}{\text{6}0}=\frac{-1\text{5}}{x+1}\)
Suy ra
(x+1).2=-15.60
2x+2=-900
2x=-900+2
2x=-898
x=-898:2
x=-449